EMA and sustainable development: role of digital transformation and business intelligence system - Latif, Badar; Ong, Tze San; Mohd Said, Ridzwana; Muhammad, Haslinah; Hanan, Abdul (Human Resource Management Academic Research Society, 2023)
Environmental management accounting (EMA) is an evolving in the recent decade and EMA approach integrates environmental and financial information within organizations to support effective environmental management decisions. With growing attention towards EMA, the concerns about sustainable development is still unclear in the academic literature. Underpinned by the dynamic capability theory, the current study aimed to fill this research gap by addressing the role of EMA on addressing sustainable performance through digital transformation and business intelligence system. Methodologically, the sample of 202 collected from manufacturing eEnterprise in Pakistan. Based on the result, the findings revealed that EMA need to mitigate the impacts of business activities on the environment and provides a valuable framework for organizations to identify, measure, and manage their sustainable performance. In addition, the role of digital transformation and business intelligence system create an avenue for the manufacturing firms to reinforce the direction towards digitalization.